Here's the question you clicked on:
ashleyb
simplify...pic is in comment box
\((a+bi)(c+di)=(ac-bd)+(ad+bc)i\) either that, or multiply out using four multiplications like you would with \((x+2)(x+5)\) and then at the end replace \(i^2\) by \(-1\)
here \(a=10,b=3, c=5,d=-2\) so first method gives \[(10\times 5-3\times (-2))+(10\times (-2)+3\times 5)i\]
sorry but im still having trouble understanding
I just FOILed and then combined like terms. So, 10 x 5 = 50, 10 x -2i = -20i, 3i x 5 = 15i, and 3i x -2i = -6i^2. Combining like terms gets me 50 - 5i -6i^2, but we then remember that i^2 = -1, so further simplifying becomes 50 - 5i + 6 ------> 56 - 5i. Did that make sense?